Numerical model of cable median barrier for crashworthiness assessment - Emir Faez Arsad
This final year project is about to design a numerical model of cable median barrier, to simulate an oblique crash of a small vehicle crash to strand cable barrier and analyze some impact parameters, velocities, deceleration, angle of impact and occupant risk.